âDIGITAL FORMALDEHYDE METERâ INOVASI PENDETEKSI KANDUNGAN FORMALIN CEPAT DAN AKURAT DENGAN TEKNOLOGI BERBASIS INSTRUMEN ELECTRONIC NOSE - SaÃ¢Â€Â™diyah, Halimatus; Regeista, Famelian; Syahwal, Alifian Juantono; Yatmo, Agung Heru (Program Kreativitas Mahasiswa - Karsa Cipta, 2013)
Design of measuring device formalin with "Digital Formaldehyde Meter" that implementation of the Electronic Nose is an alternative technology to produce quick and accurate detector. "Digital Formaldehyde Meter" is designed with a digital system, the input signal detected the sensor array TGS (TGS 2600, and 2611), and processed with the help of microcontroller and digitized by a digital LCD (Liquid Crystal Display) to digital convertor. System instrumentation is based on "Digital Formaldehyde Meter" using solid and liquid samples. Process calibration tool "Digital Formaldehyde Meter" is performed by comparison tool uv spectrometer and the test produced an average error of 2.93%.